PLURALISME DAN MULTIKULTURALISME DALAM KERANGKA KERUKUNAN ANTAR UMAT BERAGAMA PERSPEKTIF AL-QUR’AN (Telaah dan Urgensinya dalam Kajian Filsafat Sosial) - Hendri Masduki (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2018)
a system of value which see positive and optimist complexity of Religion, culture, tradition, and interaction way by acceting it as real fact and doing right based on the context of fact without have to occur distortion of theological concept privately in oeder that the spiritualism remained strong” is a very correlative idiom in study the pluralism and multiculturalism in pespektive in perspective harmony of interreligious as common patform for society of Indonesia as nation and state wich based on Pancasila with the slogan Bhinneka Tunggal Ika.